The influence of sports disciplines on the development of key competencies of future physical education teachers - Kondratska, Galyna D.; Voloshyn, Olena R.; Prots, Roman O.; Kopko, Iryna Ie.; Stets, Valentyna I. (Linguistics and Culture Review, 2021)
The reform of primary school education caused significant changes in the trajectories of the physical education. This study was aimed at identifying the ways of forming professional competencies among students as an indicator of the quality of knowledge. During the research, the following methods were used: the analysis of literature sources, laws and regulations, normative documentation, analysis, design, modeling, survey, observation, generalisation of pedagogical experience of specialists. The authors developed scientific and methodological material regarding the problem of the formation of professional competencies among students. The ways of formation of professional competencies among students were revealed. The effectiveness of the proposed approaches to the formation of professional competencies as an indicator of the quality of students’ knowledge was checked. Methodical materials and practical tasks that contain recommendations which will help teachers to create an educational environment, provide various forms of integrated learning, involve families of children in pedagogical interaction, evaluate their own practice, monitor student development were developed.